PENGARUH PENAMBAHAN SERAT BAMBU DAN PENGGANTIAN 10% AGREGAT HALUS DENGAN ABU SEKAM PADI DAN ABU CANGKANG LOKAN TERHADAP KUAT TARIK BETON - Ade Sri Wahyuni; Akayzeh Dlucef; Fepy Supriani (Universitas Bengkulu, 2019)
This study aimed to determine the effect of bamboo fiber addition and 10 % fine aggregate replacement with the mixture of Rice Husk Ash (RHA) and Sea-Shell Ash (SSA) toward the tensile strength of concrete. Bamboo fiber was used to add tensile strength in the matrix of concrete. The samples prepared were 21 cylinders, in which three samples of normal concrete were compared with 3 samples from each percentage of bamboo fiber (0.25% and 0.5%). The mixture of RHA and SSA was also divided into three different percentages i,e : 65:35 ; 50:50 and 35:65. The dimension of specimen is 15 cm in diameter and 30 cm in height. The specimen were cast and immersed in the soaking bath to be tested on day 28 in reference to the standard SK. SNI 03-2491-2002. The graph shows that, 0,5% addition of bamboo fiber with mixture of RHA and SSA 35:65, has the higher tensile strength than normal concrete (16%).